A concise history of Kentucky - Klotter, James C. (UPSO - University Press of Kentucky E-Books., 2008)
To most people, the word "Kentucky" is likely to inspire thoughts of Derby Day, burley tobacco fields, feuding Appalachian families, coal mines, and Colonel Sanders' famous fried chicken. There is much more, however, to the Bluegrass State's rich but often unexplored history than mint juleps and the Hatfields and McCoys. In A Concise History of Kentucky, authors James C. Klotter and Freda C. Klotter introduce readers to a captivating story that spans 12,000 years of Kentucky lives, from Native Americans to astronauts. All facets of Kentucky history are explored-geography, government, social s